Pengaruh Pengangguran, Pengeluaran Per Kapita, Pendidikan dan Kesehatan terhadap Kemiskinan di Provinsi Sumatera Barat - Puteri, Reski Maila; Marwan, Marwan (ARZUSIN, 2023)
The purpose of this study was to determine the effect of response, per capita expenditure, education, health on poverty in Sumatera Barat Province. This type of research is descriptive and associative, the data used is panel data where the research was conducted in Sumatera Barat in 2018-2022. This study uses the Eviews 12 application, the selected model is Random Effect. The F test shows unemployment, per capita expenditure, education and health have an effect on poverty. Whereas in the t test, unemployment has no significant positive effect on poverty, per capita expenditure has a negative effect on poverty, education has no significant negative effect on poverty and health has a significant negative effect on poverty in Sumatera Barat. From this research it is hoped that there will be synergy between the government and the community through job creation and skills debriefing in the form of training so that job seekers can have skills that are in accordance with the required field work so that they can be useful in reducing poverty levels in Sumatera Barat.